Dampak Pandemi Covid-19 terhadap Pendapatan Pedagang Pakaian di Pasar Lama Kota Banjarmasin - Desy Amalia Rivayanti; Eny Fahrati (PPJP Universitas Lambung Mangkurat, 2023)
The study aims to find out the difference in clothing merchant income in the old market of Banjarmasin City before and during the Covid-19 pandemic.This study uses T Sample Paired test data analysis technology, processed with SPSS 16. It uses primary data from interviews that are obtained directly from several samples by providing questionnaires to clothing traders in the old market. There are 36 clothing merchants. This research is quantitative descriptive research.The results of this study showed that before being affected by the Covid-19 pandemic and during the Covid-19 pandemic, there was a difference in the income of clothing merchants.